2007
DOI: 10.1209/0295-5075/80/27003
|View full text |Cite
|
Sign up to set email alerts
|

Bloch's theory in periodic structures with Rashba's spin-orbit interaction

Abstract: We consider a two-dimensional electron gas with Rashba's spin-orbit interaction and two in-plane potentials superimposed along directions perpendicular to each other. The first of these potentials is assumed to be a general periodic potential while the second one is totally arbitrary. A general form for Bloch's amplitude is found and an eigen-value problem for the band structure of the system is derived. We apply the general result to the two particular cases in which either the second potential represents a h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
48
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(60 citation statements)
references
References 13 publications
12
48
0
Order By: Relevance
“…It is similar to what has experimentally been observed for two-dimensional electron gazes [21]. Our conclusion is in agreement with what has been reached in [15]. To close this section let us note that when the magnetic field is switched off, we recover Bloch Hamiltonian amended by a free particle living on the z-direction.…”
Section: Total Spectrumsupporting
confidence: 90%
See 3 more Smart Citations
“…It is similar to what has experimentally been observed for two-dimensional electron gazes [21]. Our conclusion is in agreement with what has been reached in [15]. To close this section let us note that when the magnetic field is switched off, we recover Bloch Hamiltonian amended by a free particle living on the z-direction.…”
Section: Total Spectrumsupporting
confidence: 90%
“…Indeed, for a strong B we analyze the corresponding spectrum and symmetries to end up with different conclusions. As an interesting consequence, we show that the polarization symmetries are preserved in such case and this generalize the obtained result in [15] to the magnetic field. More importantly, such polarizations are obtained to be B-dependent and therefore it can be controlled by different values taken by the magnetic field.…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…Those studies included the effect of dimensionality and features of the band-gap structures of a gas in a superimposed periodic and arbitrary confining potentials [23], ballistic transport of electrons in periodic magnetic field [24,25], switching controlled by SO coupling [26], and quantum wire superlattices [27]. It was shown that SO coupling induced by an external periodic field leads to the appearance of new gaps, making the electronic system tunable even in the condensed matter settings.…”
mentioning
confidence: 99%